171 Habitual Sleep Duration and Chronic Pain in the US Population Over A 10-Year Period: Implications for Sleep Health Disparities. (3rd May 2021) - Craig, Chloe; Kennedy, Kathryn; Ghani, Sadia; Perlis, Michael; Seixas, Azizi; Jean-Louis, Giardin; Killgore, William; Wills, Chloe; Grandner, Michael
Abstract: Introduction: Chronic pain is linked with sleep disturbances, which worsen pain experiences. The nature of the bi-directional relationship between sleep and chronic pain has not been explored at the population level, especially among racial/ethnic minorities, a group disproportionately burdened by chronic pain. To address this gap, we investigated the relationship between sleep and chronic pain experiences in the US population and conducted race-stratified analyses. Methods: Data from the CDC National Health Interview Survey (NHIS) was used, from 2007-2016. Sleep duration was categorized as <=4hrs, 5-6hrs, 7-8hrs, 9hrs, or 10+hrs. N=298, 698 provided data for analysis. Chronic pain outcomes included arthritis, joint pain, neck pain, back pain, jaw/face pain, and migraines/headaches. Covariates included age, sex, body mass index, and employment status. Race/ethnicity was included as a covariate and interaction term, categorized as Non-Hispanic White, Black/African-American, Mexican-American, Other Hispanic/Latino, Asian/Pacific-Islander, Indian/Subcontinent, American Indian/Alaskan Native, and Multiracial/Other. Weighted logistic regression analyses examined sleep as predictor and pain as outcome, adjusted for covariates. Post-hoc analyses examined sleep-by-race/ethnicity interactions. Results: Prevalence in the population was 24.7%, 40.0%, 4.8%, 15.7%, 29.5%, and 15.0% for arthritis and joint, jaw/face, neck, back, and migraine/headache pain. In adjusted analyses compared to 7-8hrs, arthritis was more likely among <=4hrs (OR=2.6, p<0.0005), 5-6hrs (OR=1.5, p<0.0005), 9hrs (OR=1.1, p=0.002), and 10+hrs (OR=1.2, p<0.0005). Joint pain was also more likely among <=4hrs (OR=2.8, p<0.0005), 5-6hrs (OR=1.6, p<0.0005), 9hrs (OR=1.1, p=0.002), and 10+hrs (OR=1.2, p<0.0005). Jaw/face pain was also more likely among <=4hrs (OR=3.0, p<0.0005), 5-6hrs (OR=1.6, p<0.0005), 9hrs (OR=1.2, p=0.001), and 10+hrs (OR=1.4, p<0.0005). Neck pain was more likely among <=4hrs (OR=3.0, p<0.0005), 5-6hrs (OR=1.6, p<0.0005), and 10+hrs (OR=1.2, p<0.0005). Back pain was also more likely among <=4hrs (OR=3.1, p<0.0005), 5-6hrs (OR=1.7, p<0.0005), and 10+hrs (OR=1.3, p<0.0005). Migraines/headaches were also more likely among <=4hrs (OR=3.6, P<0.0005), 5-6hrs (OR=1.8, P<0.0005), and 10+hrs (OR=1.4, P<0.0005). Significant sleep-by-race/ethnicity interactions were seen for joint (p=0.002), jaw (p<0.0005), and neck (p=0.002) pain, but not back pain (p=0.08), migraines/headaches (p=0.28), or arthritis (p=0.45). Conclusion: Habitual short and long sleep are associated with a wide range of chronic pain conditions. Bidirectional relationships should be explored as a public health priority. Race/ethnicity interactions suggest that the sleep/pain experience differs by group (reasons should be explored). Support (if any): R01MD011600, R01DA051321, K24AG055602, R01AG041783